Fish disease : - Noga, Edward J. (Wiley-Blackwell, 1999)
North Carolina State Univ., Raleigh. Reprint of an original Mosby-Year Book edition, c1996. Intended to guide the reader through commonly encountered fish diseases and to provide the knowledge to management these diseases effectively. Focus is on cultured fish, but data also applies to wild populations. Color and halftone illustrations